"Yesterday once more:" IP film, phantom/fandom of music, and the youthful (re)turn of Chinese cinema in the age of new digital media. Issue 1 (12th May 2021) - Xiao, Ying
Abstract: China in the second decade of the twenty-first century has seen an upsurge of coming-of-age cinematic narratives by a cohort of Millennial filmmakers—referenced in Chinese discursively as the post-1970s or post-1980s Generation. Heralded by Zhao Wei's So Young (one of the highest grossing films in 2013), these productions feature many thematic and formal aspects of the Bildungsroman genre. Such generic features as retrospective narration and a storyline that chronicle the physical, psychological, and intellectual growth of the protagonists from youth to adulthood are employed to explore broader social-cultural transformations of China in the late twentieth and early twenty-first centuries. My paper examines the ascendance of the Chinese Millennial narrative (qingchun pian) and its distinguishing formal qualities symptomatic of intersectionality and intermediality that also define IP film in the new century and in the wake of new digital media. Through a close analysis of such examples as Lu Gengxu's Forever Young (2014) and Rene Liu's Us and Them (2018), the essay reengages and reinterprets critical discourses of Bildungsroman, nostalgia, and heterotopia by placing them in a specific contemporary Chinese context. Moreover, the subgenre/cross-genre's appeal across a broad audience and generation not only derives from its visual effects, the existing literary, theatrical resources and fanbase but also from its soundtrack and musical imagination. With a second focus on film music, the article illustrates how the creative, intricate employment and remix of Cantopop, Mandapop, Chinese campus folklore and rock music in the films represent youthfulness, authenticity, and the (ideal) past and selfhood as opposed to an alienated, postmodern reality. The contrast creates a heterotopian spatiotemporality on screen and articulates a distinctly Chinese Bildungsroman that engages with the complex, rapidly transforming network of Chinese media ecology.